Speed Tracking of Field Oriented Control Permanent Magnet Synchronous Motor Using Neural Network - Wahyu Mulyo Utomo; Nooradzianie Muhammad Zin; Zainal Alam Haron; Sy Yi Sim; Azuwien Aida Bohari; Roslina Mat Ariff; Dirman Hanafi (Institute of Advanced Engineering and Science, 2014)
The field oriented control theory and space vector pulse width modulation technique make a permanent magnet synchronous motor can achieve the performance as well as a DC motor. However, due to the nonlinearity of the permanent magnet synchronous motor drive characteristics, it is difficult to control by using conventional proportional-integral-derivative controller. By this reason in this paper an online neural network controller for the permanent magnet synchronous motor is proposed. The controller is designed to tracks variations of speed references and also during load disturbance. The effectiveness of the proposed method is verified by develop simulation model in MATLAB-simulink program. The simulation results show that the proposed controller can reduce the overshoot, settling time and rise time. It can be concluded that the performance of the controller is improved.DOI: http://dx.doi.org/10.11591/ijpeds.v4i3.5941